2011
DOI: 10.1007/s10519-011-9510-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonshared Environmental Influences on Sleep Quality: A Study of Monozygotic Twin Differences

Abstract: Research has consistently demonstrated that environmental influences are important for explaining the variability in sleep quality observed in the general population. Although there is substantial evidence assessing associations between sleep quality and a host of environmental variables, it is possible that their effects are mediated by genetic influence. A monozygotic twin differences design was used to assess the specific contribution of nonshared environmental influences on sleep quality, whilst controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 66 publications
2
29
0
1
Order By: Relevance
“…Results also supported a GxE interaction, in which genetic influences on the variation in physical health were greatest at both high and low levels of marital quality and lowest at the average level of marital quality (evidence of differential susceptibility, see Panel C of Figure 1). With respect to health behaviors, one study found that the association between marital quality and sleep quality appears to be due to nonshared environmental influences, which may again reflect the influence of one’s partner [44]. …”
Section: Findings From Studies Of Rge and Gxe And Relationship Outcomesmentioning
confidence: 99%
“…Results also supported a GxE interaction, in which genetic influences on the variation in physical health were greatest at both high and low levels of marital quality and lowest at the average level of marital quality (evidence of differential susceptibility, see Panel C of Figure 1). With respect to health behaviors, one study found that the association between marital quality and sleep quality appears to be due to nonshared environmental influences, which may again reflect the influence of one’s partner [44]. …”
Section: Findings From Studies Of Rge and Gxe And Relationship Outcomesmentioning
confidence: 99%
“…Our own research using the monozygotic twin differences design has confirmed that associations between several traditionally conceptualised 'environmental' variables are likely to intertwine with genetic factors to influence sleep. (106) More studies of this kind will enable us to understand more about the processes contributing to the associations between the environment and sleep problems.…”
Section: Specifying Genes and Environmentsmentioning
confidence: 99%
“…На основе положения, что раз-личия между МЗ близнецами порождаются не генетическими факторами, можно заключить, что причиной различий является среда и, возможно, до определенной степени ошибка измерения. Исходя из такой логики, недав-но было проведено исследование внутрипарных различий качества сна (Barclay et al, 2012a). При учете генетических и общих средовых влияний оказалось, что различия в качестве сна у МЗ близнецов были связаны с внутрипарными различиями по общему уровню здоровья у мужчин и с удовлетворенностью отношениями у женщин.…”
Section: изучение средовых факторов влияющих на сонunclassified